Implementasi Model Project Based Learning Sebagai Upaya Penumbuhan Karakter 6 Dimensi Profil Pelajar Pancasila - Kadek Windari; Ni Wayan Sudarti, S.Pd., M.Hum. (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research is a conceptual study of the implementation of the Project Based Learning learning model as an effort to grow the character of students according to the 6 dimensions of the Pancasila Student Profile in the independent curriculum. The Project Based Learning learning model is one of the learning models that can foster Pancasila values in students. By using qualitative descriptive methods through library research, this study aims to find out how the implementation of the Project Based Learning learning model as an effort to grow the character of students according to the 6 dimensions of the Pancasila Student Profile in the independent curriculum. The results of this study show that the Project Based Learning learning model is a strategy that is in accordance with the values contained in the Pancasila Student Profile.